Pendekatan Psikologi Dalam Skematik Desain Fasilitas Day Care di Kota Denpasar - Ni Putu Mely Kusuma Ningsih; I Kadek Merta Wijaya; I Wayan Widanan (Program Studi Arsitektur, Fakultas Teknik Universitas Warmadewa, 2022)
The busyness of parents in working, especially in the city of Denpasar causes not a few of them to entrust the role of child care students to Daycare Facilities, but the currently available daycare facilities and infrastructure still do not meet the eligibility and safety standards to support the growth and development of children, especially for young children. 0 – 2 years. So that by providing facilities and infrastructure that are classified according to the age grouping of children, namely ages 3 months – 2 years, ages 3 – 4 years and ages 5 – 6 years, where the 3 age groups have different characters and needs in the growing process. their flowers. The purpose of this design is to design a daycare facility that is safe and comfortable for children and provides facilities that can support the growth and development and creativity of children from an early age. By using an architectural approach to behavior, age, color psychology and shape psychology with data collection methods in the form of literature study and observation and presentation methods, namely: compilation and classification of data. The design concept used is Kiddy Town with a building that is realized with a post modern design theme. Which produces 3 types of facilities, namely the main facilities, support and services tailored to the needs of users.